Spectrohotometric Determination of Cobalt and Palladium After Extraction of their n-Amylthioglycolate Complexes into Chloroform - Kumar Malik, Ashok; Gupta, Usha; Rao, A.L.J. (Asian Journal of Chemistry, 2010)
Cobalt and palladium react quantitatively with n-amylthioglycolate (ATG) to form water insoluble coloured complexes in the pH range 8.0–10.0 and 4.0–8.0, respectively. As the equilibrium is established rapidly, these complexes can be extracted into chloroform. The colour of the complexes is quite stable. The pink coloured cobalt complex has λmax at 500 nm while the yellow coloured palladium complex absorbs maximum at 380 nm. Beer's law is obeyed over the concentration ranges 0.092–0.825 ppm and 0.50–4.93 ppm, for cobalt and palladium, respectively. The molar absorptivities and Sandell's sensitivities for the two complexes are 3.2 x 104 1 mol–1 cm–1 and 0.73 x 104 1 mol–1 cm–1, and 0.00164 μg Co cm–2 and 0.0145 μg Pd cm–2, respectively. Then replicate determinations on sample solution containing 5.9 μg of cobalt and 43.5 μg of palladium gave mean absorbance 0.32 and 0.30, with relative standard deviations of 3.09% and 3.05%.